Digital Identity Card: Between Public Services And Community Needs (Case Study: Disdukcapil Of Cirebon Regency) - Gatot Santoso; Rifzika Ayunda Cahyani; Yanto Heryanto (PT Publikasiku Academic Solution, 2024)
This research focuses on implementing the Digital ID Card in Cirebon Regency, with a case study at the Population and Civil Registration Office (Disdukcapil). The primary purpose of this study is to analyze the effectiveness of digital ID cards as a form of public service and the extent to which they meet the community's needs. The research method used is a qualitative case study, with data collection techniques through in-depth interviews, participatory observation, and document analysis. The study results show that implementing the Digital ID Card in Cirebon Regency has increased the efficiency and accessibility of population administration services. However, there are challenges regarding socialization, technological infrastructure, and varying levels of people's digital literacy. This research also found that Digital ID Cards are more effective in meeting the needs of people with adequate access to digital technology. The conclusion of this study shows that further development is needed to increase the acceptance and accessibility of Digital ID cards, including improving technological infrastructure and digital education programs for the community. This research has implications for more inclusive and technology-based public policymaking.